Yield curve modeling and forecasting : the dynamic Nelson-Siegel approach - Diebold, Francis X., 1959-; Rudebusch, Glenn D., 1959- (Econometric and Tinbergen Institutes lectures., 2013)
Understanding the dynamic evolution of the yield curve is critical to many financial tasks, including pricing financial assets and their derivatives, managing financial risk, allocating portfolios, structuring fiscal debt, conducting monetary policy, and valuing capital goods. Unfortunately, most yield curve models tend to be theoretically rigorous but empirically disappointing, or empirically successful but theoretically lacking. In this book, Francis Diebold and Glenn Rudebusch propose two extensions of the classic yield curve model of Nelson and Siegel that are both theoretically rigorou.